P412 White cell count (WCC) and mean corpuscular volume (MCV) as surrogate markers for thiopurine monitoring in inflammatory bowel disease (IBD) treatment: A single-centre experience. (16th January 2018) - Christopher, B; Altamimi, K; Campbell, N; Rynne-Lyons, R; Alakkari, A; O'Connor, A; McNamara, D; Breslin, N; Ryan, B
Abstract: Background: Thiopurines (TPs) are commonly used in treatment of IBD. Optimal dosing is determined by patients' weight and commonly titrated to achieve target range of 2–2.5 mg/kg. Levels of 6-thioguanine nucleotide (6-TGN), an active metabolite breakdown of thiopurines and 6-methylmercaptopurine (6-MMP), an inactive metabolite, can be measured to check for efficacy and toxicity, respectively, but this is not widely available. WCC, lymphocyte count (LC) and MCV have emerged as surrogate markers to monitor TP efficacy. Previous studies have suggested WCC<4 × 10 9 /l and MCV > 100 fl correlate with 6-TGN level and reduced risk of disease relapse. The aim of our study is to assess these surrogate parameters in our patients on TPs. Methods: A total of 200 IBD patients being treated with azathioprine (AZA) were included in this retrospective, observational study. Data were obtained from our IBD database and review of medical notes. Recent WCC, LC, and MCV were recorded, along with body weight, AZA dose and concomitant treatment with biologic therapy (mainly anti-TNF agents). Disease activity index was assessed using Harvey Bradshaw index (HBI) for Crohn's disease (CD) and partial Mayo score for ulcerative colitis (UC) at time of blood testing. Results: There were 108 (54%) females and 92 (46%) males. Of the 200 patients, 144 (72%) were diagnosed with CD, 55 (27.5%) UC and 1(0.5%) indeterminate colitis. One hundred and seventeen patients (58.5%) were on AZA monotherapy with 83 patients (41.5 %) on combination therapy with a biologic. The mean age for our study population was 49 (19–81). The mean WCC count was 6.81 × 10 9 /l (2.8–14.2). Mean LC was 2.86 × 10 9 /l (0.5–8.8) with mean MCV of 91.1 fl (78–104). Seven of 200 (3.5 %) patients had WCC < 4 × 10 9 /l and 7 of 200 (3.5%) also had a MCV > 100 fl. In the IBD AZA monotherapy group, 4 of 117 patients (3.4%) had leucopoenia and the same number 4 of 117 had macrocytosis and only one patient (0.9%) had both leucopoenia and macrocytosis. In patients on combination therapy, 3 of 83 (3.6%) had leucopoenia and the same number of patients, 3 of 83, demonstrated macrocytosis. None in this group had both leucopoenia and macrocytosis. The mean AZA dose to body weight was 1.7 mg/kg. The mean HBI score was 2.9 and partial MAYO score 1.7. Conclusions: A very small percentage of our study population had leucopoenia, lymphopenia or macrocytosis suggesting that many may be sub-therapeutic. Notwithstanding this, the majority of patients were in clinical remission. There was no significant difference in these measured parameters between the AZA monotherapy or combination therapy groups. It is not clear how assiduous we should be in escalating TP dose to target MCV and WCC/LC in order to maximise efficacy in IBD patients. Work is underway to correlate these surrogate markers with TP metabolites levels and disease activity indices.